“Isutan Jarat” A Traditional Game to Improve Perception and Autism Concentration in the Barito Riverside - Yuwono, Imam (Department of Special Education, 2019)
The difficulty of finding media to play in the Barito Riverside Stream, affects the low level of autistic children in the development of perception, attention, and communication because of those aspects. This study aims to determine the effectiveness of traditional games Isutan Jarat to help the development of autistic children. The single subject research method with the design of cross variable multiple baselines are used to reveal the effect of treatment or intervention on the target behavior. The results of data analysis show that the traditional game Isutan Jarat Effective Line is used to improve the perception, attention, and concentration of autism. Based on the findings of this study, it is recommended that the Isutan Jarat game is used as an alternative play media for autistic children in the Barito Riverside Stream.